A Dynamic Model Of Contractor-induced Delays In India - Das, Dillip Kumar; Emuze, Fidelis (Penerbit Universiti Sains Malaysia, 2017)
To understand delays in the Indian construction context, an exploratory survey was conducted as a precursor to the development of simulation models. System Dynamics (SD) was used to visualise the pivotal feedback relations that cause delays to evolve mechanisms that reduce it. A community development construction project in India serves as the case for modelling. Findings of the study suggest that definite causal feedback relations exist among difficulties in financing the project, ineffective planning and scheduling, poor communication and coordination by the contractor, conflict between the contractor and other stakeholders and use of inappropriate construction methods and construction delays. However, the modelling efforts reveal that the use of these best practices can reduce delay significantly: provision of adequate project finances and cash flow, effective planning and scheduling, adoption of appropriate construction methods and contingencies for rework in the schedule.